Hadis Tematik Tentang Etika Komunikasi Islam: Tanggung Jawab, Saling Menghormati, dan Kritik Konstruktif - Mohd Rafiq (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Communication Ethics can be understood broadly because the ethical content is very dense. However, what determines whether a communication is ethical or unethical is the fundamental values/norms that are used as the main reference. If it is in Islam, then whether the communication is ethical or not (Islamic Communication) will, of course, be measured by the standard values/norms contained in the Qur’an and the Hadith of the Prophet. A Muslim can be said to have good ethics in communicating if the manners and content of his communication follow the rules outlined by Allah and his Messenger. He always pays attention to the values of good and bad, what is appropriate and what is inappropriate, what is useful and what is useless. In other words, he does not violate what Allah and the Messenger of Allah prohibit. On the other hand, a Muslim is considered to have no ethics if he communicates with other people but does not heed the rules contained in the Qur’an and Sunnah. Specifically, the study of ethics from the perspective of the Prophet's hadith is the main study regarding responsibility, constructive criticism, and mutual respect.